(untitled) (Research, Society and Development, 2023)
Introduction: Periodontal disease is very common during pregnancy and has been associated with adverse pregnancy outcomes, such as premature birth. However, systematic reviews show conflicting results about this possible relationship. Objective: To summarize the evidence on the impact of periodontal disease on low birth weight preterm infants. Methodology: This is a narrative review of the literature with an exploratory character about the relationship between periodontal disease and the risk of premature birth and low birth weight. Pubmed, Google Scholar and Scielo databases were used with the descriptors: “Gingivitis”, “Periodontitis”, “Low birth weight newborn”, “Oral health” and “Premature delivery”. Discussion and Results: The vast majority of studies reveal that there is a relationship between periodontal disease and premature birth, however, the indication is maintained by research that deepens knowledge and analyzes other factors that may be involved. Conclusion: Periodontal disease may be one of the possible risk factors for premature birth and low birth weight. However, more precise studies with a randomized clinical trial and sufficient follow-up time should be performed to confirm the association.